Dysosteosclerosis: Clinical and radiological evolution reflecting genetic heterogeneity - DEMİRCİOĞLU, SERAP; GÜRPINAR TOSUN, BUŞRA; GÜRAN, TÜLAY; BEREKET, ABDULLAH; ALAVANDA, CEREN; ARMAN, AHMET (My University, 2022)
Dysosteosclerosis (DSS), the term coined in 1968 for ultrarare dysplasia of the skeleton featuring platyspondyly with focal appendicular osteosclerosis, has become generic by encompassing the genetic heterogeneity recently reported for this phenotype. We studied four unrelated Turkish patients with DSS to advance understanding of the new nosology. Patient 1 suffered femur fractures beginning at age 1 year. DSS was suspected from marked metaphyseal osteosclerosis in early childhood and subsequently platyspondyly accompanying patchy osteosclerosis of her appendicular skeleton. She harbored in SLC29A3, in 2012 the first gene associated with DSS, a unique homozygous duplication (c.303_320dup, p.102_107dupYFESYL). Patient 2 presented similarly with fractures and metaphyseal osteosclerosis but with no platyspondyly at age 2 months. She was homozygous for a novel nonsense mutation in SLC29A3 (c.1284C>G, p.Tyr428*). Patient 3 had ocular disease at age 2 years, presented for short stature at age 11 years, and did not begin to fracture until age 16 years. Radiographs showed mild platyspondyly and focal metaphyseal and femoral osteosclerosis. She was homozygous for a unique splice site mutation in TNFRSF11A (c.616+3A>G). Patient 4 at age 2 years manifested developmental delay and frequent infections but did not fracture. He had unique metadiaphyseal splaying and osteosclerosis, vertebral end-plate osteosclerosis, and cortical thinning of long bones but no mutation was detected of SLC29A3, TNFRSF11A, TCIRG1, LRRK1, or CSF1R associated with DSS. We find that DSS from defective SLC29A3 presents earliest and with fractures. DSS from compromised TNFRSF11A can lead to optic atrophy as an early finding. Negative mutation analysis in patient 4 suggests further genetic heterogeneity underlying the skeletal phenotype of DSS. (c) 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; BONE TURNOVER; COLONY STIMULATING FACTOR; METAPHYSEAL SCLEROSIS; OSTEOCALCIN; OSTEOPETROSIS; OSTEOSCLEROSIS; PYLE DISEASE; SKELETAL DYSPLASIA; TCIRG1; TNFRSF11A; CSF1R; FRACTURES; RANK; RANKL; RECEPTOR ACTIVATOR OF NUCLEAR FACTOR KB; DEVELOPMENTAL DELAY; DUAL-ENERGY X-RAY ABSORPTIOMETRY; HYPERCALCEMIA; LRRK1; METABOLIC BONE DISEASE; METAPHYSEAL DYSPLASIA; MUTATIONS; IDENTIFICATION; OSTEOMYELITIS; DISORDERS; DYSPLASIA; NOSOLOGY; SUBUNIT; FORM